Improving 3D ultrasound prostate localisation in radiotherapy through increased automation of interfraction matching. (August 2020) - Grimwood, Alexander; Rivaz, Hassan; Zhou, Hang; McNair, Helen A.; Jakubowski, Klaudiusz; Bamber, Jeffrey C.; Tree, Alison C.; Harris, Emma J.
Highlights: Automated matching improves accuracy and precision of ultrasound guided radiotherapy. Image registration software lowers setup errors and sonography training requirements. Spatial regularisation improves registration algorithm performance. Abstract: Background and purpose: Daily image guidance is standard care for prostate radiotherapy. Innovations which improve the accuracy and efficiency of ultrasound guidance are needed, particularly with respect to reducing interobserver variation. This study explores automation tools for this purpose, demonstrated on the Elekta Clarity Autoscan®. The study was conducted as part of the Clarity-Pro trial (NCT02388308). Materials and methods: Ultrasound scan volumes were collected from 32 patients. Prostate matches were performed using two proposed workflows and the results compared with Clarity's proprietary software. Gold standard matches derived from manually localised landmarks provided a reference. The two workflows incorporated a custom 3D image registration algorithm, which was benchmarked against a third-party application (Elastix). Results: Significant reductions in match errors were reported from both workflows compared to standard protocol. Median (IQR) absolute errors in the left–right, anteroposterior and craniocaudal axes were lowest for the Manually Initiated workflow: 0.7(1.0) mm, 0.7(0.9) mm, 0.6(0.9) mm compared to 1.0(1.7) mm, 0.9(1.4) mm, 0.9(1.2) mm for Clarity. Median interobserver variation was ≪0.01 mm in all axes for both workflows compared to 2.2 mm, 1.7 mm, 1.5 mm for Clarity in left–right, anteroposterior and craniocaudal axes. Mean matching times was also reduced to 43 s from 152 s for Clarity. Inexperienced users of the proposed workflows attained better match precision than experienced users on Clarity. Conclusion: Automated image registration with effective input and verification steps should increase the efficacy of interfraction ultrasound guidance compared to the current commercially available tools.